KOMPONEN KIMIA ORGANIK LIMA JENIS ASAP CAIR - Nur Adi Saputra; Sri Komarayati; Gusmailina (Jurnal Penelitian Hasil Hutan, 2021)
Plants such as cacao (Theobroma cacao), avocado (Persea americana), puspa (Schima wallichii), sengon(Falcataria mollucana) and tarik angin (Usnea sp.) are widely planted in the community for fruit or wood needs.Periodically, they harvest these types of wood for common uses or plant rotation purposes. In general, wood sorting is usedfor simple construction or even conventionally burned. In addition to conventional combustion techniques to produce charcoal,there is another product that can be produced, namely liquid smoke - using a combustion technique by adding a condenserto produce liquid smoke. Liquid smoke contains organic chemicals with various benefits. This study investigates the organicchemical content of liquid smoke of cacao, avocado, puspa, sengon, and tarik angin wood. The five types of materialswere carbonized using a pyrolysis reactor around 400oC. Liquid smoke was obtained by condensing fumes mechanism.Analysis of organic liquid chemical using Gas Chromatography Mass Spectrometer (GCMS) Pirolisys Type QP2010and High Performance Liquid Chromatography (HPLC). GCMS analysis showed that cacao liquid smoke has thehighest concentration of acidic group, of the 45.53%, where the concentration of acetic acid was 31.81%. The presence ofthe highest phenol group was in avocado liquid smoke as much as 56.86%, where the concentration of phenol compoundsreached 41.92%. The acid and phenol groups are type of compounds contained in liquid smoke and have a lot of benefits.